Julgamento de quem? Imagens de mulheres no discurso dos processos de estupro em São Luís – MA - PASSOS, Kennya Regyna Mesquita (2017)
ABSTRACT: The research aims to study how the Criminal Justice System in the District of São Luís - MA participates in the gender device, as an instance of power-knowledge, to construct discursively the feminine subjectivity during the investigation of the crimes of rape among the Years from 2010 to 2015. The importance of gender as a category of analysis for the understanding of a given social reality and the need to adopt this perspective in the studies about the Criminal Justice System as a way of coping with the phenomena of violence And discrimination against women, starting with the dialogue between the Criminal Sciences and other branches of knowledge such as Sociology and Discourse Analysis, broadening the understanding of the functioning of this system, identifying the ideological substrates that support the application of norms and Legal concepts, in spite of the apparent technicality and neutrality of judicial discourse, Thus going scientific and politically with the improvement of the institutions of the Justice System and consequently with the jurisdictional rendering.